The Application of Mindfulness Practices in the High School Choral Classroom to Impact Music Performance Anxiety During Solo Performance - (:unkn) unknown (My University, 2021)
Music students are regularly expected to perform in front of live audiences as part of their music education. These public performances can cause music students to experience music performance anxiety (MPA). Some of the impacts of MPA that could potentially impact the quality of their performance include fear, dread, shaking, trembling, and dry mouth. One possible intervention to counteract the negative effects of MPA is through practicing mindfulness. Mindfulness is the practice of being aware and in the present moment without fear, shame, or judgment of self or others. This mixed-methods research study addressed the prevalence of music performance anxiety in adolescent choir students and explored using a mindfulness curriculum as one possible intervention to decrease MPA. The purpose of this study was to determine if implementing a mindfulness curriculum in the high school choir classroom would decrease the MPA of the students while performing solo repertoire. Students in a rural high school in the Midwest (N=14) participated in an 8-week mindfulness intervention titled Learning to BREATHE developed for adolescents. Prior to the intervention, the participants took a survey to assess their music performance anxiety levels. During the intervention, students filled out a workbook to track their mindfulness experiences and prepared a vocal solo. Following the intervention, students performed a vocal solo in front of a small audience of peers and then took the same survey to assess their music performance anxiety levels. The analysis of the student workbook materials provided information used to select five case studies. These five participants provided further perspectives on mindfulness and music performance anxiety in adolescent vocal musicians. Four themes emerged from the study which include (1) the prominence of MPA in adolescent vocal musicians; (2) the impact of MPA on student performances; (3) the absence of mindfulness in adolescents; and (4) the impacts of the mindfulness curriculum, both musical and nonmusical. Findings aligned with past studies indicating that mindfulness practice can help decrease MPA in musicians, however age and gender did not appear to follow as predictors of MPA levels. The subjects in this study all experienced MPA at varying levels. Music teachers should be aware of how MPA can impact a performance and find methods to counteract the effect it has on their students.
Keywords: adolescent; choir; high school; mindfulness; music performance anxiety; school